2013
DOI: 10.1159/000343205
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Knife Surgery for Refractory Insular Cortex Epilepsy

Abstract: Background: Resection of the epileptogenic insular cortex is surgically challenging. We sought to evaluate the potential of Gamma Knife® surgery (GKS) for the treatment of pharmacoresistant insular cortex epilepsy (ICE) in patients who underwent GKS between 2005 and 2010. Adverse events and effects on seizure frequency were assessed. Methods: Three cases of refractory ICE were treated by GKS between 2005 and 2010. Results: Case 1 had refractory nonlesional ICE, proven by depth electrodes only partially helped … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 83 publications
(59 reference statements)
1
12
0
Order By: Relevance
“…Barbaro et al [12] randomized patients by dose; they demonstrated that the higher dose arm had better outcomes (within statistical power limits). This same effect was found in other small series underlining the tendency of higher doses to have a better antiepileptic effect than lower doses [40][41][42][43]. Maesawa et al [44] showed in a rat model, that SRS controlled epilepsy accompanied by stabilization of memory compared with untreated epileptic rats without causing subsequent behavioral impairment, for high (60 Gy) as well as low dose (30 Gy), supporting the hypothesis that even this relatively lower dose RT could be effective.…”
Section: Discussionsupporting
confidence: 62%
“…Barbaro et al [12] randomized patients by dose; they demonstrated that the higher dose arm had better outcomes (within statistical power limits). This same effect was found in other small series underlining the tendency of higher doses to have a better antiepileptic effect than lower doses [40][41][42][43]. Maesawa et al [44] showed in a rat model, that SRS controlled epilepsy accompanied by stabilization of memory compared with untreated epileptic rats without causing subsequent behavioral impairment, for high (60 Gy) as well as low dose (30 Gy), supporting the hypothesis that even this relatively lower dose RT could be effective.…”
Section: Discussionsupporting
confidence: 62%
“…Thermoablations combined with cortectomies reportedly resulted in up to 80% of patients achieving seizure freedom, with 20% experiencing postoperative complications (including 5% of permanent morbidity); however, the additional value of combining both procedures was undetermined . Finally, radiosurgery is described as promising; however, this series is currently limited to three patients, with favorable outcome in two . Notably, one patient postoperatively developed new spells, with a feeling of evisceration, genital pain, and head/right hemibody athetoid movements occurring in clusters.…”
Section: Discussionmentioning
confidence: 99%
“…44 Finally, radiosurgery is described as promising; however, this series is currently limited to three patients, with favorable outcome in two. 45 Notably, one patient postoperatively developed new spells, with a feeling of evisceration, genital pain, and head/right hemibody athetoid movements occurring in clusters. All these innovative techniques emphasize the difficulties and the functional risks inherent to surgery for insular epilepsies.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, different neuronal systems may have different radiosensitivities [22]. However, the GK parameters used in the present series (volume: 1.6-3.18 cm 3 , marginal dose: 24 Gy) are similar to a series of 3 published cases of insular epilepsy [17], which treated volumes of 1.2-3.2 cm 3 with a marginal dose of 20 Gy.…”
Section: Discussionmentioning
confidence: 99%
“…A recent case series described significant seizure reduction in 2 out of 3 patients treated with GK for pharmacoresistant epilepsy involving insular cortex [17]. However, use of GK in the primary motor cortex has not previously been described.…”
Section: Introductionmentioning
confidence: 99%